Extraction Process of Precedent Study in the Student Studio Scheme - Pakiding, Hana Ardina Putri; Hayati, Arina; Novianto, Didit (Journal of Architectural Design and Urbanism, 2024)
A precedent is a piece of design knowledge that acts as an input to the design process. On the other hand, the originality of architectural design is built from many interpretations that occur within the designers, including the performance in the precedent study. However, more information still needs to be provided about how students seek, read, and apply precedents during the naturally occurring design process. Architecture students have limitations in developing a design, considering they need more experience and knowledge than practitioners. This research is based on the learning-by-doing experienced by architecture students when designing a housing project. The research is conducted with the participant of second-year architecture students, which includes observation during the studio class and interview. The portfolio documents are also used to support the data itself. The result shows that architectural precedents are sought almost in every phase of the design process. The precedent that has already been seen or even analyzed becomes part of the designer’s tacit knowledge.